Students’ Problems in Using English Pronouns at Junior High School Number 15 Jambi - Fitriana Fitriana; Wennyta Wennyta; Siti Aisyah (Universitas Batanghari Jambi, 2022)
This study aims to find out what are the students' problems in using English pronouns in using personal and possessive pronouns at SMP Negeri 15 Jambi. In this study, this research used qualitative research. The subjects of this study were class VIIG students of SMP Negeri 15 Jambi in the academic year 2021/2022. All problems in the use of pronouns have been categorized and identified, namely subject, object, possessive adjective, and possessive pronoun. In simple terms, the students face more problems in using object pronouns. This can be seen from the percentage results where the problem of using object pronouns is 35.2%, questions are answered incorrectly. Meanwhile, at least students face problems in using possessive pronouns by 14.4%. The result of this research found that the seventh grade students of SMP Negeri 15 Jambi mostly face the problem of using object pronouns, which is the most difficult thing for students because they do not really understand how to use object pronouns.